Enslaved Women in America: From Colonial Times to Emancipation - West, Emily (Rowman & Littlefield Publishers, 2014)
West offers an overview of the lives of enslaved women in America by using a broad chronological perspective, considering themes and issues in their lives from the colonial era through to the end of the Civil War. She compares the lives of enslaved women—sometimes exceptional and sometimes ordinary—across time and space with the lives of enslaved men, and with the white men and women who held them in bondage. West draws upon a wide range of evidence in evaluating enslaved women's lives and considers the major methodological issues they pose in order to build a composite, or overall, picture of enslaved womanhood through "snapshots'' of different women at various stages of their life-cycles.